The Prevalence of Fibromyalgia Among Medical Students at King Abdulaziz University: A Cross-Sectional Study - Samman, Abeer A (Cureus, 2021)
Background and objective Fibromyalgia (FM) is a chronic, multifactorial pain condition. The latest literature suggests that genetic and environmental factors including continuous stress contribute significantly to FM's pathophysiology. In this study, we aimed to investigate the prevalence of FM among medical students as they are considered a population significantly at risk of developing the condition. Methods This cross-sectional study was conducted at King Abdulaziz University. Medical students included in the study were recruited through a random stratified sampling method. A self-administered questionnaire was distributed to the participants; it included questions related to widespread pain index (WPI) and symptom severity scale (SSS) to assess the symptoms and diagnosis of FM, which were established based on the current diagnostic criteria. All first-year students were excluded from this research. Results A total of 450 participants were recruited for the study. Among them, 291 (64.7%) were females and 159 (35.3%) were males. Their ages ranged from 18 to 26 years, and the mean age was 21.52 years (SD: ±1.52). They came from different academic levels: 97 (21.6%) were in the second year, 79 (17.6%) were in the third year, 70 (15.6%) were in the fourth year, 99 (22%) were in the fifth year, and 105 (23.3%) were in the sixth year. The overall prevalence of FM was found to be 43 (9.6%). It was established based on the number of students who fulfilled the diagnostic criteria or were previously diagnosed with FM by a professional physician. Conclusion FM is highly prevalent among medical students. Our findings demonstrate the likelihood of the influence of medical school on causing the condition, as it has a stressful education system with high academic expectations. We recommend that this issue be seriously addressed since FM leads to a significant burden on the students and can negatively affect their future medical practice.